Graduación en el Teatro Melico Salazar. (UNED, 2016)
Luis Guillermo Carpio Malavasi - Rector en el podio. Aparecen en la mesa principal María Graciela Núñez Núñez, Gisele Bolaños Mora, Ronald Bonilla Carvajal - Escritor, Katya Calderón Herrera y Nelson José Briceño Vargas